Historical Criticism of the Hermeneutical Approach in the Interpretation of the Qur'an - Islam, Muhammad Thoriqul; Noorhidayati, Salamah; Novitasari, Dwiana; Ikmah, Amit Dana; Nasution, Alhafidh; Azmi, M. Ulul; Aulia, Tsabata Firman; Mushaffa, Arju (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Hermeneutics is a classic theme that remains relevant in Islamic scholarly discourse, particularly in the debate over its use in interpreting the Qur'an. There are three main views among Muslim scholars and ulama: those who reject it completely, those who accept it completely, and those who accept it with certain limitations. This debate is rooted in the origins of hermeneutics, a discipline developed by Western scholars to interpret biblical texts that raise issues of authority and authenticity. This study aims to explore the hermeneutic approach from a historical perspective through a literature study and thematic analysis, employing steps of comparison, contrast, and criticism. The results show that, from the perspective of Qur'anic interpretation, hermeneutics is viewed as a Western product originating from the Christian theological tradition and developed within a modern philosophical framework emphasizing the historicity and relativity of textual meaning. Therefore, this approach is not entirely in line with the principles of Islamic interpretation emphasizing the sanctity, absolute authority, and authenticity of divine revelation. Furthermore, hermeneutics is also considered contrary to the methodology of Ulumul Qur'an, which has clear procedures and hierarchies of interpretation based on Islamic sources. This study confirms the relevance of historical criticism of Qur'anic hermeneutics as a scholarly effort to restore Qur'anic interpretation to an authentic Islamic epistemological framework. Thus, this study makes a new contribution to strengthening the methodology of interpretation based on the principles of the sacredness of revelation, the integrity of divine meaning, and the scientific discipline of Ulumul Qur'an, originating from the Islamic tradition itself.